PENERAPAN FUZZY INFERENCE SYSTEM UNTUK KEBERHASILAN PENGGUNAAN ANIMASI INTERAKTIF TINGKAT SEKOLAH DASAR - Samudi Samudi (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2016)
Obstacles encountered in the teaching-learning process leads to launch the lack of communication between teachers and students. In this case, teachers should be more creative in applying learning methods. A similar thing happened in North Tugu SDN 01 Morning North Jakarta, where it takes an educational media to enhance the interest and attention of the students to support the learning process in schools, especially information technology media such as educational games. With the game, an application is expected to provide benefits and knowledge for students of SDN 01 Morning North Tugu North Jakarta on the introduction of the 32 provinces in Indonesia. The use of information technology in teaching and learning as well as introducing the world of animated multimedia interactive learning.